CALCULATION OF PRODUCTIVITY TOOLS AND EQUIPMENT CONVEYANCE UNLOADING WORK IN GALLEY HEAP PT. PAMAPERSADA NUSANTARA DISTRICT ABKL KUTAI REGENCY EAST KALIMANTAN - JUPRIADI SUMULE, THOMAS (KURVA S JURNAL MAHASISWA, 2014)
PT. Pamapersada Nusantara (PAMA) is one of the companies engaged in coal mining by open pit processing system (open pit) to the area of about 8.5 h. In the process of stripping the overburden of work (overburden), it is necessary to do the analysis and evaluation in the selection of tools and how the willingness of the condition of the tool to be used in the mining process so that the productivity targets can be achieved.Productivity is the ability of the tool in a unit time (m3 / h), and heavy equipment is one very important factor in the work of the mine in order to assist and facilitate human in doing his job. And to support the achievement of productivity, it is very necessary to be considered in the care management of used heavy equipment. Productivity depends on the capacity of the tool, the tool cycle time (cycle time), the efficiency of the tool, the harmony in the use of tools.For data that is used there are two, namely, the primary data is data obtained directly in the field of the processes that occur in the field as a data cycle time and documentation. While secondary data is the data obtained from PT. Pamapersada ABKL districts such as data reporting unit, production data plan, actual production data, and rainfall data.From the results of calculations it can be concluded that the productivity of excavator loading Komat'su brand PC 1250 is 446.30 Bcm / Hour and monthly production is 1992.579,33 Bcm, productivity tools Komat'su push DZ 375 is 415.70 Bcm / Hour and production is 181,868.75 Bcm per month, and the average productivity for conveyance brand Komat'su HD 785 is 102.78 Bcm / Hour. As for compatibility tool (match factor) already sesui so no time digging tool or instrument awaiting unloading transports the queue too long. Number of conveyances required for 1 unit of excavator Komat'su PC 1250 is 5 units of dump trucks Komat'su HD 785 and to push the tool in place heaping 1 unit Komat'su DZ 375 bulldozer.